2017
DOI: 10.4172/2473-3350.1000438
|View full text |Cite
|
Sign up to set email alerts
|

Integrated GIS and AHP for Marine Aquaculture Site Selection in Penghu Cove in Taiwan

Abstract: Journal of Coastal Zone Management AbstractMarine cage culture has been developed quickly in recent years from land-based operation transfer to marine cage culture by government policy in Taiwan. Therefore, the suitable site selection is an important premised and key factor for successful marine cage culture and sustainable development in the future. Especially, it's greatly influences economic viability by determining capital outlay and affecting running costs, production and mortality. Hence, the decision fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The ebb and flood tides were considerably larger around the northwestern and southern PHI (grids 45-47), indicating that the water mass changed quickly in a short time. However, in the coastal area of the inner bay (grids 19, 25, and 40), the variation of the ebb and flood tides was smaller, indicating that the ocean conditions changed less rapidly [45]. Furthermore, the areas identified in this study had considerably fewer cold-water InDs, which indicated that they were suitable locations for cobia cage culture.…”
Section: Discussionmentioning
confidence: 75%
“…The ebb and flood tides were considerably larger around the northwestern and southern PHI (grids 45-47), indicating that the water mass changed quickly in a short time. However, in the coastal area of the inner bay (grids 19, 25, and 40), the variation of the ebb and flood tides was smaller, indicating that the ocean conditions changed less rapidly [45]. Furthermore, the areas identified in this study had considerably fewer cold-water InDs, which indicated that they were suitable locations for cobia cage culture.…”
Section: Discussionmentioning
confidence: 75%
“…An integrated approach based on spatial multi-criteria evaluation (SMCE) was adopted using analytic hierarchy process (AHP) and weighted linear combination (WLC) to select suitable polygons for fish farming (Pérez et al, 2003;Pérez et al, 2005;Dapueto et al, 2015;Aguilar-Manjarrez, et al, 2017;Shih, 2017). Then, the carrying capacity concept was used to determine the most suitable fish farm number.…”
Section: Site Selection Methodologymentioning
confidence: 99%
“…A list of required factors, commonly used in marine fish farming site selection, have been established (Pérez et al, 2003;Pérez et al, 2005;Szuster & Hatim., 2010;Dapueto et al, 2015;Micael et al, 2015;Aguilar-Manjarrez, et al, 2017;Shih, 2017;Gimpel et al, 2018) in addition to the national technical documents implemented for aquaculture planning. Then, significant factors were selected according to their suitability to cage culture, mainly related to the three target fish species (seabass, seabream and common meagre) in M'diq bay according to local conditions, and in compliance with national legislation and local rules in force.…”
Section: Site Selection Methodologymentioning
confidence: 99%
“…Peer judgment -a comparison method of the analytic hierarchy process -is a practical and useful method to assist decision making that ensures consistency across all of the options considered. It involves ranking the attributes against each other to assess their relative importance; that technique has been used in recent decades in many applications related to multi-criteria decision making (Shih 2017). The use of questionnaire can synthesize the views of different people who have different roles and perform different activities at several levels (e.g., policy makers, government planners, scientists, farmers, private industry representatives, and local authorities).…”
Section: Al 2021)mentioning
confidence: 99%